Measuring women’s agency in agroecological food systems transformation - Renduchintala, Swati (CIFOR-ICRAF, 2023)
Agro-ecology-based natural farming has emerged as a sustainable and socially just alternative to the “green revolution”-based food systems. The Andhra Pradesh Community-managed Natural Farming programme (APCNF) has been driving the agro-ecological movement in India from conventional farming to nature-based solutions. With 630,000 farmers enrolled to date, the program credits the social movement of women self-help groups and their federations as the crucial ingredient for transformation. This paper looks at the work in APCNF in academic lenses to answer: “Do women collectives and their federations play a substantial role in enabling and improving women’s agency by transformation to natural farming?” The agency is measured by the decision-making abilities of women in Andhra Pradesh to trace the journey of transformation through: Why did they decide to transform to natural farming? When did they decide to initiate this shift to natural farming? Who helped them in this process of shift? How did they begin the process of transformation? Where did they start and continue with the transformation? So, we determine “does feminization of agro-ecology help in improving the agency of women?” which in turn helps in scaling agro-ecology. Through in-depth study and data from the three major agroclimatic zones of Rayalseema, Delta areas and tribal areas, this paper also explores the gradients of women across geographies and social strata. The findings of the paper would help in establishing focused gender-based policy for sustainable food systems transformations. It also paves a path to explore the agency beyond the farmgate in value chains and beyond.